Bad Bugs Move Alike: Regional Transmission of Antibiotic-Resistant Organisms. (October 2020) - Wang, Joyce; Foxman, Betsy; Pirani, Ali; Lapp, Zena; Mody, Lona; Snitkin, Evan
Abstract : Background: Upon admission, 56.8% of patients entering 6 Michigan nursing facilities from regional acute-care hospitals (ACHs) were colonized with 1 or more antibiotic-resistant organisms (AROs) (Mody 2018, CID). This observation raises 2 questions critical to regional infection control strategies: (1) Is the high ARO burden entering nursing facilities driven by dominant epidemic lineages or diverse circulating strains? and (2) What are the relative roles of patient characteristics (eg, high-risk patients) and exposure to specific ACHs (eg, high-risk facilities) in determining whether patients are colonized with AROs upon nursing facility admission? Here, we integrated whole-genome sequencing, patient transfer, and clinical data to answer these questions for the 4 most prevalent ARO species in the region: methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus faecalis (VREfc), Enterococcus faecium (VREfm), and ciprofloxacin-resistant Escherichia coli (CipREc). Methods: We studied colonizing isolates collected via active surveillance of 584 patients in 6 Michigan nursing facilities between 2013 and 2016. The whole genome of the first isolate of each ARO species collected from each patient was sequenced and analyzed to identify sequence types (STs) and to infer the transmission network by species. We determined the connectedness between nursing facilities based on the number of patients received from the same ACHs and assigned each ARO to the most recent ACH using curated transfer information. The associations between patient characteristics and recent ACH exposures with colonization by ARO were examined using multivariable models. Results: Most of the sequenced ARO isolates belonged to major healthcare-associated lineages: MRSA (ST5, N = 78 of 117); VREfc (ST6, N = 68 of 75); CipREc (ST131, N = 50 of 64); and closely related VREfm isolates (N = 129). Phylogenetically closely related isolates were found across study facilities, indicating that endemic ARO lineages have permeated local healthcare networks (Fig. 1). Patient characteristics played a dominant role in determining patient risk of ARO colonization on admission to a nursing facility. Only in the case of VREfm was a hospital significantly associated with colonization after adjustment for covariates (Table 1). Conclusions: ARO lineages were widely disseminated and colonization of specific ARO lineages at nursing facility entry could not be attributed to recent exposure to a specific ACH. Thus, for the ARO lineages studied here, a broader transmission system crosses ACHs, nursing facilities and probably the community. Therefore, the best indicators of ARO colonization were patient clinical characteristics, particularly poor functional status and antibiotic exposure. These findings suggest that intervention efforts targeting patients with characteristics associated with ARO colonization may help limit further spread among regional facilities. Funding: None Disclosures: None